The Use of EdrawMind Map Application to Generate Student's Idea in Speaking - Audina, Izza; Eva Savitri, Wiwiet (LPPM Universitas Pancasakti Tegal, 2022)
Speaking skills might be one of the most difficult skills to master because too many ideas are stuck and a lot lack vocabulary to explain and produce. This study describes the process of digital mind mapping as the media and tools for arranging ideas in speaking. This method can promote students’ speaking skills through analyzing, arranging, and creating to improve their speaking performance. This study aims to investigate how EdrawMind is used to generate ideas in speaking and the effect of using online mind mapping to generate students’ ideas in speaking. There have been several studies conducted in developing mind mapping in writing, but yet little research has explored the use of mind mapping in students’ speaking and how mind mapping can increase speaking ability by generating an idea in a good organization. Furthermore, EdrawMind as the new online mind mapping application is explored related to the use of mind mapping in a speaking context. A qualitative method with four Phases: Pre-Test, Treatment, Post-Test, and speech performance valuation are used in the data collection. Senior high school students are for the subject using semi-structured Interviews, worksheets (speech text), and presentations. The data are analyzed and transcribed into descriptions and explanations.